2014
DOI: 10.1103/physrevb.90.085201
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the exciton dynamics inDCM2:Alq3

Abstract: We study the temperature dependence of the triplet and singlet exciton dynamics in the archetype small molecule fluorescent guest-host system, tris(8-hydroxyquinolinato) aluminum (Alq 3 ) doped with 4-(dicyanomethylene)-2-methyl-6-julolidyl-9-enyl-4H-pyran (DCM2). We develop a comprehensive model of the exciton dynamics, and use it to fit the transient photoluminescence under different pulsed optical pumping in the temperature range of 80 K< T< 295 K. The triplet decay has a significantly different temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…E.g., Hoffmann et al [36] found that the temperature dependence of triplet diffusion in conjugated polymers is best described by Marcus theory, with a transition to MA theory at lower temperatures. A similar conclusion was drawn by Liu et al for diffusion in the disordered fluorescent small-molecule host-guest system consisting of tris(8-hydroxyquinolinato) aluminum (Alq 3 ) doped with 4-(dicyanomethylene)-2methyl-6-julolidyl-9-enyl-4H-pyran (DCM2) [21]. However, for metalorganic phosphorescent emitter molecules, it is presently not clear which of these approaches is most accurate, which type of transfer process (Förster or Dexter) is predominant, and to what extent information about the detailed diffusion mechanism can be gained by studying the guest concentration and temperature dependence of the diffusion-related efficiency loss due to, e.g., concentration quenching or TTA.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…E.g., Hoffmann et al [36] found that the temperature dependence of triplet diffusion in conjugated polymers is best described by Marcus theory, with a transition to MA theory at lower temperatures. A similar conclusion was drawn by Liu et al for diffusion in the disordered fluorescent small-molecule host-guest system consisting of tris(8-hydroxyquinolinato) aluminum (Alq 3 ) doped with 4-(dicyanomethylene)-2methyl-6-julolidyl-9-enyl-4H-pyran (DCM2) [21]. However, for metalorganic phosphorescent emitter molecules, it is presently not clear which of these approaches is most accurate, which type of transfer process (Förster or Dexter) is predominant, and to what extent information about the detailed diffusion mechanism can be gained by studying the guest concentration and temperature dependence of the diffusion-related efficiency loss due to, e.g., concentration quenching or TTA.…”
Section: Introductionsupporting
confidence: 79%
“…Triplet exciton diffusion has been extensively studied for purely organic neat-film materials that are commonly used as a host, as an electron or hole transport layer, or a fluorescent emissive layer [20][21][22][23][24]. Due to the long triplet lifetime in such materials and the small intermolecular distances, the diffusion lengths can be of the order of 100 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). 68,74,75,79,81,[88][89][90]92,93,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] Since triplet excitons undergo diffusion via short range Dexter energy transfer, the number of available hopping sites quickly becomes limited during the downhill migration. In strongly disordered systems sometimes one observes a blue shift of the maximum of phosphorescence spectrum upon cooling below 100 K. 103,104 Using theoretical modeling Beljonne, Ko ¨hler, and co-authors showed that in materials with high degree of disorder, certain thermal activation is needed for triplets to find lower energy sites, resulting in the blue shift of PL spectrum upon cooling.…”
Section: Diffusion Equationmentioning
confidence: 99%